(untitled) (REMUNOM, 2023)
The lack of designs, as well as the design empirical, in various areas of civil engineering are a recurring problem in the daily lives of small and medium-sized construction companies. And this factor is enhanced when a specific construction site operation area needs for designs​​. The formworking and reshoring steps are examples of underestimated dimensioning factors in a work. In this way, a mobile application was developed aimed at wood formwork design for shoring solid or lattice slabs, based on the technical standards ABNT NBR 15696 and ABNT NBR 7190, the application was designed in order to capture user inputs, relating to the characteristics of the shoring and the structural element. Thus, the application is able to carry out the checks contained in the standards and later dimension the struts regarding the use load and own weight of the structural elements, and from there, deliver a formwork project containing the quantity and position of the shorings, rate of use of the struts in terms of loading, and an interface that is easy to use and access by any user with engineering knowledge.